Factores psicosociales que inciden en el consumo de drogas en trabajadoras sexuales que acuden al centro de salud – Centro Histórico. - López Proaño, Gabriela Elizabeth (2021)
This research would provide in the study of drug use in the sex workers who go to the clinic of Historic Center. Thus, this research will approach from analyze of social, culture, political problems and psychosocial factors which affects sex workers who use drugs. The research will analyze this problematic from the correlation of variables that allow to deep the problem of drug use in sex workers. The results of the research become a reference that serves to carry out future research of an academic, scientific, and social nature. From the demographic and psychosocial analysis of the 110 sex workers who work in the surroundings of the Historic Center in the Quito city. It will be known which substances they consume the most and how often they do so. This will be done from the analysis of both socio-demographic and psychosocial data and related to drug use, etc. The research will approach the problem from the descriptive and quantitative analysis of the variables that will allow answering the questions: ¿Which are the factors that influence drug use in sex workers who go to the health center? and ¿What are the drugs that sex workers use the most? Drug use is commonly associated as an effective stimulant that allows people evade a hostile reality, inhibit feelings of discomfort such as acts of abuse and violence, and in some cases to face exploitation and abandonment. The drugs they use the most are alcohol, marijuana, tobacco, cocaine, etc.